واقع المرأة المسلمة في المجتمعات المعاصرة: ماليزيا نموذجاً - Ali Saged, Ali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
This article discusses some of the contemporary issues pertaining to Muslim women and their role in society as well as their involvement and contribution to the development of the society. Women are part of the community. Hence, thoughts and contributions of women along with men are like a partner in life. The presence of women cannot be ignored because without them, survival of the ummah will not be achieved that resulted in a loss to the nation, religion and country. Therefore, this article attempts to highlight an initial review of the contribution of Muslim women to society, particularly in Malaysia in developing and innovating in the sector of employment and family life which led to nation-building and the new generation. Apparently, Malaysian women have been able to work together along with the men for advancing the economic and political contributions and social development in Malaysia.